Analisis Efektivitas Saluran Sekunder Blang Bintang Daerah Irigasi Krueng Aceh Kabupaten Aceh Besar - Riandy Ferdila Putra; Meliyana Meliyana; Muhammad Zardi (Jurnal Teknik Sipil Unaya, 2021)
Irrigation area is a unit of land that gets water from an irrigation network. One of the Krueng Aceh irrigation dams built to irrigate the Krueng Aceh irrigation area is divided into 2 parts, namely the right irrigation area, to irrigate an area of 7,194 ha, consisting of 6,385 ha located on the right bank of Krueng Aceh and 809 ha located on the left hand side Krueng Aceh. While the left irrigation area, to irrigate an area of 256 ha. The research location is in the Secondary Channel Blang Bintang BBB.4 - BBB.5 Krueng Aceh Irrigation Area Aceh Besar District. Based on the analysis that has been done, the maximum evapotranspiration needs value is occurred in August which is 2.98 mm / day, with an average evapotranspiration requirement of 2.63 mm / day. The maximum value of plant consumptive use needs occurred in April, which was 8.44 mm / day. The maximum effective rainfall value for rice occurs in December in the first half month (December-1), which is 1.32 mm / day. The maximum water requirement in paddy fields is found in April the second half of the month (April-2) which is 8.02 mm / day, with the need for water at the gates which is 1.43 l / sec / ha. The level of effectiveness of Blang Bintang secondary channel on BBB.4 - BBB.5 channels is 80.58% (0.81).